Field Survey and Monitoring of Potato Tuber Moth (Phthorimaea operculella)(Zeller)(Lepidoptera: Gelechiidae) - Tiwari, DB; Thapa, RB; Shrestha, SM; Joshi, SL (Journal of the Institute of Agriculture and Animal Science, 2006)
Potato tuber moth (PTM), Phthorimaea operculella (Zeller) is a major pest of stored potato. Field survey was conducted to know the effect of this pest on potato production and storage under farmers' conditions in the Kathmandu valley and remote district Rolpa during 2005. Ninety farmers (40 in the Kathmandu valley and 50 in Rolpa) were interviewed in semi-structured questionnaires and PTM was also monitored using sex pheromone. Survey and monitoring revealed that PTM (insect pest) and late blight (disease) were the major problems of potato crop in both the areas. Maximum of 69 moths per week were collected in one set of pheromone trap in Kathmandu and 76 moths trapped within five days of trap setting in Rolpa. That was the first record, authentic evidence to clarify farmers’ confusion in Rolpa district about the presence of P. operculella in potato growing areas. In the Kathmandu valley, 95% of respondent farmers were aware of this pest and 80% farmers relied on chemical pesticides to manage P. operculella on stored potato. However, only 4% of the respondent farmers in Rolpa were aware of this pest. Therefore, its management is necessary for healthy potato production in the field and storage under farmers’ conditions in Nepal. Key words : Phthorimaea operculella, field survey and monitoring J. Inst. Agric. Anim. Sci. 27:157-160 (2006)